Mechanical Testing of Mouse Carotid Arteries: from Newborn to Adult - Amin, Mazyar (MyJove Corporation, 2012)
The large conducting arteries in vertebrates are composed of a specialized extracellular matrix designed to provide pulse dampening and reduce the work performed by the heart. The mix of matrix proteins determines the passive mechanical properties of the arterial wall(1). When the matrix proteins are altered in development, aging, disease or injury, the arterial wall remodels, changing the mechanical properties and leading to subsequent cardiac adaptation(2). In normal development, the remodeling leads to a functional cardiac and cardiovascular system optimized for the needs of the adult organism. In disease, the remodeling often leads to a negative feedback cycle that can cause cardiac failure and death. By quantifying passive arterial mechanical properties in development and disease, we can begin to understand the normal remodeling process to recreate it in tissue engineering and the pathological remodeling process to test disease treatments. Mice are useful models for studying passive arterial mechanics in development and disease. They have a relatively short lifespan (mature adults by 3 months and aged adults by 2 years), so developmental(3) and aging studies(4) can be carried out over a limited time course. The advances in mouse genetics provide numerous genotypes and phenotypes to study changes in arterial mechanics with disease progression(5) and disease treatment(6). Mice can also be manipulated experimentally to study the effects of changes in hemodynamic parameters on the arterial remodeling process(7). One drawback of the mouse model, especially for examining young ages, is the size of the arteries. We describe a method for passive mechanical testing of carotid arteries from mice aged 3 days to adult (approximately 90 days). We adapt a commercial myograph system to mount the arteries and perform multiple pressure or axial stretch protocols on each specimen. We discuss suitable protocols for each age, the necessary measurements and provide example data. We also include data analysis strategies for rigorous mechanical characterization of the arteries.